Comparison of Proangiogenic Effects of Adipose-Derived Stem Cells and Foreskin Fibroblast Exosomes on Artificial Dermis Prefabricated Flaps - Jiachao Xiong; Zhixiao Liu; Minliang Wu; Mengyan Sun; Yu Xia; Yuchong Wang (Stem Cells International)
Large prefabricated flaps often suffer from necrosis or poor healing due to a lack of new blood vessels and related factors that promote angiogenesis. The innovative use of adipose-derived stem cell exosomes (ADSC-Exo) resolves the problem of vascularization of prefabricated flaps. We analyzed the differential microRNA (miRNA) expression in ADSC-Exo using next-generation sequencing (NGS) technology to explore their potential mechanisms in promoting vascularization. We observed that ADSC-Exo could significantly promote the vascularization of artificial dermis prefabricated flaps compared with human foreskin fibroblast exosomes. NGS indicated that there were some differentially expressed miRNAs in both exosomes. Bioinformatics analysis suggested that significantly upregulated hsa-miR-760 and significantly downregulated hsa-miR-423-3p in ADSC-Exo could regulate the expression of the ITGA5 and HDAC5 genes, respectively, to promote the vascularization of skin flaps. In summary, ADSC-Exo can promote skin-flap vascularization, and thereby resolve the problem of insufficient neovascularization of artificial dermis prefabricated flaps, thus expanding the application of prefabricated skin-flap transplantation.